Typical Mistakes of Lithuanian Students in the use of English Words - Aprijaskytė, R.; Pareigytė, E. (Kalbotyra, 1972)
In this paper an attempt is made to analyse and classify the most common mistakes of Lithuanian students in word usage caused by the interference of the learner’s mother tongue. The analysis of mistakes, that have been observed while teaching students majoring in English, shows that most mistakes are due to the difference in the semantic structure of words and to different combinability in the English and Lithuanian languages.Mistakes due to the difference in the semantic structure of words in both languages occur: (a) when the student gives the English word a non-existing meaning, transferring one of the meanings of the corresponding polysemantic Lithuanian word to the English word; b) when the student endows an English word with the meaning peculiar only to its etymological equivalent current in Lithuanian.Mistakes due to different combinability in English and Lithuanian appear: (a) when the learner, violating certain rules of combinability in English, broadens the usage of the English word (in accordance with the combining capacity of the corresponding word in Lithuanian); (b) when the student translates certain lexical units word for word, ignoring phraseological unity and government.An analysis and classification of mistakes caused by the interference of the learner’s mother tongue may serve as a kind of basis for making up exercises to eliminate and prevent those mistakes.